2015
DOI: 10.18632/oncotarget.6240
|View full text |Cite
|
Sign up to set email alerts
|

P2X3 purinergic receptor overexpression is associated with poor recurrence-free survival in hepatocellular carcinoma patients

Abstract: P2 purinergic receptors are overexpressed in certain cancer tissues, but the pathophysiologic relevance of purinergic signaling in hepatocellular carcinoma (HCC) remains unknown. To examine the role of P2 purinergic signaling in the pathogenesis of HCC and characterize extracellular nucleotide effects on HCC cell proliferation, two independent HCC patient cohorts were analyzed for P2 purinergic receptor expression, and nucleotide treated HCC cell lines were evaluated for effects on proliferation and cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Therefore, it might not be the best candidate receptor for the inhibitory effects observed in this study. Although P2X3 receptor was also a common receptor among CCA cell lines and MMNK-1, it was recently reported to induce cell proliferation in hepatocellular carcinoma cell lines and to be associated with poor recurrence-free survival in patients (36). On the other hand, P2Y6, P2Y13, and P2X7 are the receptors that are expressed in CCA cells, but not in immortalized cholangiocarcinoma cells (MMNK-1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might not be the best candidate receptor for the inhibitory effects observed in this study. Although P2X3 receptor was also a common receptor among CCA cell lines and MMNK-1, it was recently reported to induce cell proliferation in hepatocellular carcinoma cell lines and to be associated with poor recurrence-free survival in patients (36). On the other hand, P2Y6, P2Y13, and P2X7 are the receptors that are expressed in CCA cells, but not in immortalized cholangiocarcinoma cells (MMNK-1).…”
Section: Discussionmentioning
confidence: 99%
“…P2X3R overexpression has been shown to promote proliferation via the JNK pathway in hepatocellular carcinoma and to be associated with an unfavorable prognosis. 133 The role of P2X3R in proliferation is intriguing as this receptor is rapidly desensitizing in the presence of physiological ATP concentrations, thus it seems that either in tumor cells its desensitization is defective or the TME contains factors that prevent its desensitization. The P2X5R is heavily expressed in human basal cell and squamous carcinomas, and is associated with differentiation, suggesting that its activation might indeed counteract cancer cell growth.…”
Section: Atp Receptors In Cancermentioning
confidence: 99%
“…Numerous studies have demonstrated that P2 receptors involve in cancer cells and are expressed to a very high level in some cases, such as P2X3, P2X5, P2X7 and P2Y2 and P2Y442, 80, 81, 82, 83 (Table 1). In terms of clinical evaluation, P2X3 receptor overexpression was reported to be associated with poor recurrence-free survival in hepatocellular carcinoma patients 84 .…”
Section: Altered Ca2+ Channels/transporters In Cancermentioning
confidence: 99%